2016
DOI: 10.1371/journal.pone.0152936
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Short-Wavelength Blue Light in Dry Eye Patients with Unstable Tear Film Improves Performance on Tests of Visual Acuity

Abstract: PurposeTo investigate whether suppression of blue light can improve visual function in patients with short tear break up time (BUT) dry eye (DE).MethodsTwenty-two patients with short BUT DE (10 men, 12 women; mean age, 32.4 ± 6.4 years; age range, 23–43 years) and 18 healthy controls (10 men, 8 women; mean age, 30.1 ± 7.4 years; age range, 20–49 years) underwent functional visual acuity (VA) examinations with and without wearing eyeglasses with 50% blue light blocked lenses. The functional VA parameters were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 23 publications
0
29
0
1
Order By: Relevance
“…After 19 duplicates were removed, we screened the remaining 99 references and obtained the full‐text reports of 15 references for further assessment. Twelve of these were eliminated (see Table of Excluded Studies in File S2 and three RCTs that met the a priori criteria for inclusion were included in the final analysis (see Characteristics of Included Studies in File S3. We did not identify any on‐going studies from our searches of the clinical trials registries.…”
Section: Resultsmentioning
confidence: 99%
“…After 19 duplicates were removed, we screened the remaining 99 references and obtained the full‐text reports of 15 references for further assessment. Twelve of these were eliminated (see Table of Excluded Studies in File S2 and three RCTs that met the a priori criteria for inclusion were included in the final analysis (see Characteristics of Included Studies in File S3. We did not identify any on‐going studies from our searches of the clinical trials registries.…”
Section: Resultsmentioning
confidence: 99%
“…15 In this study, we aimed to evaluate the efficacy of blue-light shield eyewear and blue-light cut LEDs on glucose and lipid metabolism, as well as anthropometric data. We have previously reported that blue-light shield eyewear was beneficial in protecting against retinal damage, 16 reducing eye fatigue, 17 relieving dry eyes, 18 and improving sleep quality. 4 The eyewear used in this study more strongly reduces blue light than those we used previously.…”
mentioning
confidence: 99%
“…Since younger generations spend a significant part of their day looking at various screens highly emitting in the blue spectrum [13,14], this "rejuvenation" is not surprising. Indeed, there are numerous studies describing the appearance and/or worsening of DED signs and symptoms in visual display users [15][16][17][18]. The global pathogenesis of DED as well as the relationship between DED and exposure to visible light specifically are still not clear [19].…”
mentioning
confidence: 99%